2002
DOI: 10.1016/s0022-0248(02)01253-8
|View full text |Cite
|
Sign up to set email alerts
|

Growth of InBixSb(1−x) films on GaAs(001) substrates using liquid phase epitaxy and their characterization

Abstract: The growth of epitaxial InBi x Sb ð1ÀxÞ (x ¼ 4 atomic %) layers on highly lattice mis-matched semi-insulating GaAs substrates has been successfully achieved via the traditional liquid phase epitaxy, as a result of optimizing several growth parameters such as III/V mass ratio, growth temperature, cooling rate, etc. Scanning electron micrograph shows sharp interface even at 1 mm resolution. The grown films are n-type in the entire temperature range. The typical value of the carrier density is 9:2 Â 10 16 /cm 3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The bandgap of InSbBi film is confirmed to shift to long wavelengths with Bi content by measuring photovoltaic response of a p-n junction. The bandgap reduction determined by optical absorption measurements is about ∼35 meV/% Bi [181]. InSbBi is also grown by MOCVD [24,29,182].…”
Section: Insbbi and Quaternary Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…The bandgap of InSbBi film is confirmed to shift to long wavelengths with Bi content by measuring photovoltaic response of a p-n junction. The bandgap reduction determined by optical absorption measurements is about ∼35 meV/% Bi [181]. InSbBi is also grown by MOCVD [24,29,182].…”
Section: Insbbi and Quaternary Alloysmentioning
confidence: 99%
“…For example, Iwanowski et al [28] grew InSbBi layers by LPE with a Bi content of 0.5%. Dixit et al [181] reported growth of InSbBi with a Bi content up to 4% by LPE on GaAs substrates.…”
Section: Insbbi and Quaternary Alloysmentioning
confidence: 99%
“…Contrary to the behavior of bulk InSb [18], the carrier mobility does not increase with the measurement temperature. This anomaly in temperature-dependent electron mobility has been observed in InSb layers grown on GaAs substrate [19][20][21] and in InSb 1−x Bi x grown on GaAs substrate [7]. This behavior can be attributed to the effect of dislocations near the InSb/GaAs interface.…”
Section: Electrical Measurement: Hall Concentration and Mobilitymentioning
confidence: 60%
“…growth temperature of 360 • C-380 • C and V/III ratio of about 1.2-1.5. However, we found that equation (7) is not able to fully describe the transition from n-to p-type conductivity as shown in figures 3(a) and (b). It is likely that the dislocation and point defects formed under such low growth temperature have resulted in a dislocation type donor concentration, N D,dis and a background donor concentration, N D,bkg .…”
Section: Be-doped Insb 1−x Bixmentioning
confidence: 82%
See 1 more Smart Citation